Comprehensive Physiology 2016
DOI: 10.1002/cphy.c160005
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Signaling and the Hypothalamic‐Pituitary‐Adrenal Axis

Abstract: The elucidation of Δ9-tetrahydrocannabinol as the active principal of Cannabis sativa in 1963 initiated a fruitful half-century of scientific discovery, culminating in the identification of the endocannabinoid signaling system, a previously unknown neuromodulatory system. A primary function of the endocannabinoid signaling system is to maintain or recover homeostasis following psychological and physiological threats. We provide a brief introduction to the endocannabinoid signaling system and its role in synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 158 publications
(216 reference statements)
4
75
0
3
Order By: Relevance
“…These very interesting findings suggest that 2-AG is brain-derived and driven by excitatory signaling, which is consistent with considerable data that glutamate increases 2-AG synthesis (Hillard, 2015). These findings are also consistent with the role of 2-AG to reduce HPA axis activation (Hillard et al, 2016). It is interesting that circulating 2-AG concentrations and measures of positive emotion were not associated in this study, given the evidence below that 2-AG has been found in other studies to be negatively associated with symptoms of depression.…”
Section: Circulating Endocannabinoids and Chronic Sns Or Hpa Axis Actsupporting
confidence: 90%
“…These very interesting findings suggest that 2-AG is brain-derived and driven by excitatory signaling, which is consistent with considerable data that glutamate increases 2-AG synthesis (Hillard, 2015). These findings are also consistent with the role of 2-AG to reduce HPA axis activation (Hillard et al, 2016). It is interesting that circulating 2-AG concentrations and measures of positive emotion were not associated in this study, given the evidence below that 2-AG has been found in other studies to be negatively associated with symptoms of depression.…”
Section: Circulating Endocannabinoids and Chronic Sns Or Hpa Axis Actsupporting
confidence: 90%
“…Moreover, besides the hippocampus, other brain regions such as the prefrontal cortex, amygdala (Hill et al, 2010 ), nucleus accumbens (Bosch-Bouju et al, 2016 ), the paraventricular nucleus of the hypothalamus (Wamsteeker et al, 2010 ), lateral habenula (Park et al, 2017 ) and the periaqueductal gray matter (Moreira et al, 2009 ), are involved in stress-induced behavioral and neuroplastic consequences. These regions are modulated by eCBs and, therefore, are also potential therapeutic targets for cannabinoid drugs (For additional information about this topic, please read the excellent reviews by Gorzalka and Hill ( 2009 ), Riebe and Wotjak ( 2011 ), Hillard et al ( 2016 ), Lutz et al ( 2016 ) and Balsevich et al ( 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that stress-induced HPA axis activation and consequent corticosterone release modulate the production of eCB and CB 1 function (Hillard et al, 2016 ), it is possible that cannabinoids and glucocorticoids interact to control stress responses. Glucocorticoid hormones and their receptors (mineralocorticoid-MR and glucocorticoid receptors-GR) are abundantly expressed in the hippocampus (Herman et al, 1993 ), where, together with eCBs, they control the negative feedback regulation of the HPA axis (Hillard et al, 2016 ). Several pieces of evidence indicate that glucocorticoids and the eCB system interact to control emotional, physiological, and adaptive responses to stress.…”
Section: Stress Modulation Of Ecb Signaling In the Hippocampusmentioning
confidence: 99%
“…eCBs have been heavily implicated in modulation of the physiological and behavioral sequelae of stress exposure, particularly with respect to neuroendocrine aspects of the stress response (for a more in-depth review on this subject see Hillard et al (2016); Lutz et al (2015); Morena et al (2016b)). With respect to the HPA-axis, eCB signaling appears to be an important modulator of activation and termination of the HPA-axis function.…”
Section: Cannabinoids and Ptsdmentioning
confidence: 99%